THE EFFECT OF MULTICULTURALISM AND CULTURAL DIVERSITY ON INNOVATIVE WORK BEHAVIOR WITH CULTURAL INTELLIGENCE AS MEDIATION - Alden Neslon; Devita Revyani; Agustinus Setyawan (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2022)
This study aims to determine the effect of multiculturalism and cultural diversity on innovative work behavior by mediating cultural intelligence. Organizations in international business require every individual working in a global work environment to have cross-cultural skills or cultural intelligence. This study collects data by distributing questionnaires to expatriates and Indonesians from other cities (different ethnicity, culture, race, and language). Respondents who were sampled were employees of shipping consulting companies and shipyards in Batam City. The sampling technique used the theory of Hair et al, 2010 with a minimum sample of 95. After collecting the results from the respondents, the authors tested the data using PLS software. Based on the results of the PLS test, the authors can conclude that there is a significant relationship or not from several variables in this study. The results of this study emphasize the importance of having or studying cultural intelligence (CQ). Cultural intelligence will greatly assist us in communicating and expressing various ideas and mindsets of people from other cultures, which will have an effect on creating innovative work behaviors and creative solutions